MODBUS Standard Based SCADA System in Power Generation System - Sofyan, Yusuf; Fitriani, Sofy; Nurdin, Muhamamd Irfan (Politeknik Sukabumi, 2025)
Remote Terminal Unit (RTU) is a vital control tool in the electricity industry, facilitating various jobs, including controlling Electric Power Generation Systems (SPTL). This research aims to implement SPTL Simulator control using the Supervisory Control and Data Acquisition and Distributed Control System (SCADA and DCS). The RTU can be connected to a Master Terminal Unit (MTU) equipped with Human Machine Interface (HMI) software. The advantages include real-time process monitoring, alarm history, security, and summaries that enable efficient monitoring and analysis. The RTU used is the Generic type (Gecon) with HMI software development using Visual Studio. The use of RTU and HMI is expected to improve the performance of the SPTL simulator. The system consists of several components: Variable Speed Driver (VSD), electric motor, generator, automatic voltage regulator (AVR), F/V Controller, dummy load, sensors, meters, RTU, and communication media. The results of operational testing show that the system has worked according to design without any problems or bugs occurring. Then, based on the results of system testing with gradual loading from 0%, 25%, 50%, 75%, and 100%, it shows that, in general, the system has worked well, where the transition from dummy load to main load functions well without any residual load stored in both loading systems. The stability of the frequency and cos phi values also shows good values, where the difference is minimal for frequency (0.2 Hz), and the cos phi value is consistent at 0.99.